Studies on rubber–filler interaction in carboxylated nitrile rubber through microhardness measurement - Mandal, U.K; Aggarwal, S (Polymer testing, 2001)
The influence of carbon black filler loading on the microhardness characteristics of two types of carboxylated acrylonitrile butadiene rubber (XNBR) vulcanizates having different (ionic or covalent) crosslinking reaction systems has been studied. The microhardness measurement predicts that the rubber–filler interaction in the ionic crosslinking system is higher than that in the covalent crosslinking system. The high hardness values and strong rubber–filler interaction in the ionic crosslinking system has been explained on the basis of ionic cluster formation for the carboxylate salt in XNBR. The microhardness measurement result helps to evaluate the rubber–filler interaction and shows good correlation with the dynamic mechanical result. The theoretical predicted data deviate highly in the ionic crosslinking system, although there is a good correlation in the covalent crosslinking system.